Shaking Table Array Tests of an Ultra-High-Voltage Cup-Type Transmission Tower-Line System - Fei Wang; Ke Du; Jingjiang Sun; Fuyun Huang; Zhenghui Xiong (Shock and Vibration)
Ultra-high-voltage (UHV) cup-type transmission towers supported with long-span transmission lines are unavoidably subjected to the coupling action between the towers and the transmission lines. Therefore, investigating how tower-line coupling affects UHV cup-type transmission towers is important. In this study, three shaking table array tests of an UHV cup-type transmission tower-line system were carried out to investigate the dynamic characteristics of the coupling action between the towers and transmission lines based on the following four comparative models: a single-tower model, a single-tower model with suspended lumped masses, a three-tower-two-line model, and a five-tower-four-line model. The test results demonstrated that the tower-line coupling interaction had a significant effect on the dynamic characteristics and seismic responses, as the suspended conductor line and the suspended lumped mass decreased the frequency of the transmission tower. Under longitudinal ground motion, the model with the suspended lumped mass had the lowest peak acceleration response and the largest peak displacement response. Under the same ground motion, the four models had similar peak strains in the longitudinal direction. Under transverse-the-line ground motion, the model with the suspended lumped mass had the lowest peak acceleration response and the smallest peak responses for displacement and strain in the transverse direction; therefore, this model is inappropriate for the simulation and seismic evaluation of transmission tower-line systems.